2012
DOI: 10.1038/onc.2012.357
|View full text |Cite
|
Sign up to set email alerts
|

Flotillins as regulators of ErbB2 levels in breast cancer

Abstract: Amplification and overexpression of the receptor tyrosine kinase ErbB2 occur in up to 30% of human breast cancers, and high ErbB2 levels are correlated with poor prognosis for breast cancer patients. In contrast to the epithelial growth factor receptor (ErbB1), ErbB2 is not downregulated by ligand-induced mechanisms. Here we show that flotillins are involved in the stabilization of ErbB2 at the plasma membrane. In SKBR3 breast cancer cells and breast cancer tissue, a positive correlation between flotillin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 41 publications
11
84
0
1
Order By: Relevance
“…Although flotillins clearly mediate the clustering or the stabilization of various proteins, such as APP (Schneider et al, 2008), EGF receptor (EGFR) (Amaddii et al, 2012) and the ligand-less EGFR family member ErbB2 (Pust et al, 2013) at the plasma membrane, under some circumstances, they could also induce their endocytosis. It will therefore be important to elucidate the molecular pathways that govern the functions of flotillin in either stabilization or endocytosis of plasma membrane proteins.…”
Section: Effect Of Flotillins On Cadherin Endocytosismentioning
confidence: 99%
See 3 more Smart Citations
“…Although flotillins clearly mediate the clustering or the stabilization of various proteins, such as APP (Schneider et al, 2008), EGF receptor (EGFR) (Amaddii et al, 2012) and the ligand-less EGFR family member ErbB2 (Pust et al, 2013) at the plasma membrane, under some circumstances, they could also induce their endocytosis. It will therefore be important to elucidate the molecular pathways that govern the functions of flotillin in either stabilization or endocytosis of plasma membrane proteins.…”
Section: Effect Of Flotillins On Cadherin Endocytosismentioning
confidence: 99%
“…In particular, it will be interesting to determine whether flotillin overexpression influences the cross-talk between cadherins and EGFRs, because activation of signaling pathways downstream of EGFRs, particularly of Rho GTPases, which are key regulators of tumor cell migration and invasion (Vega and Ridley, 2008), induces cadherin destabilization (Fukata and Kaibuchi, 2001;Lanzetti et al, 2000). Interestingly, in breast and gastric tumors, flotillin 2 expression positively correlates with the expression of the EGFR ErbB2 Zhu et al, 2013), and, in these cells, flotillin 2 has been shown to stabilize this receptor at the plasma membrane (Pust et al, 2013). Moreover, flotillin 1 is required for the activation of EGFRdependent signaling, both with regard to EGFR phosphorylation and subsequent MAPK activation (Amaddii et al, 2012).…”
Section: Disease Relevance Of Flotillin-mediated Roles At Adhesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flotillin-1 palmitoylation is known to be required for its plasma membrane targeting (Liu et al, 2005;Morrow et al, 2002) and for protein kinase C (PKC)-induced endocytosis of dopamine transporter (Cremona et al, 2011). Recently, it has been shown that flotillin-1 and/or flotillin-2 can mediate receptor endocytosis, recycling and lysosomal targeting (Cremona et al, 2011;Pust et al, 2013;Solis et al, 2013). However, the regulatory role of flotillin palmitoylation in the intracellular trafficking and activation of IGF-1R is unknown.…”
Section: Introductionmentioning
confidence: 99%